PENDAMPINGAN DAN PELATIHAN TEKNIK BENDING TRIPLEK DALAM PENGGUNAAN KLEM “F” - Prabani Setio, Stefanus; Widyastuti, Maria (Jurnal Abdimas Musi Charitas, 2024)
This community service activity aimed to enhance motor skills of people with disabilities. Involving 28 participants from three communities in Semarang and Surabaya, the activity provided training in plywood bending using "F" clamps. Observations showed varying abilities: participants with excessive supervision demonstrated 0.25 normal strength, those without special supervision 0.50, and independent individuals achieved 0.9-1.0. These results indicate that independence in daily activities contributes to better motor skill development. The activity emphasized the importance of balancing protection with opportunities for people with disabilities to develop motor skills through light daily activities.